Whispers in the mist - Coates, Darcy (Coates, Darcy. Black winter, 2020)
"Clare and Dorran may have survived the city, but their relief is only temporary. Dorran is sick, and rapidly worsening. Clare fears the only way to save him might lie in the mysterious Evandale research station, supposedly one of the few remaining human refuges. But the station is three days' journey, and Clare isn't certain that their small group can endure that long. Because they not only need to survive the hollows... but survive each other. The new world has left scars, and not all of them are physical. As Clare fights to protect the most precious people in her life, she begins to realize a horrible truth: not everyone can be saved, and sometimes true monsters wear a human smile."--